2017
DOI: 10.1093/jnci/djw268
|View full text |Cite
|
Sign up to set email alerts
|

History of Keratinocyte Carcinoma and Risk of Melanoma: A Prospective Cohort Study

Abstract: Background: The association between history of keratinocyte carcinoma (KC, also known as nonmelanoma skin cancer) and risk of developing invasive melanoma has not been assessed comprehensively using prospective data. Methods: We followed 91 846 women in the Nurses' Health Study (NHS; 1984-2010, 114 918 women in the NHSII , and 48 946 men in the Health Professionals Follow-up Study (1986-2010 for diagnoses of KC and melanoma biennially. Cox proportional hazards models were used to compute hazard ratios (HRs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
2
19
1
1
Order By: Relevance
“…Other personal history of cancers included seminoma (n = 2), bladder (n = 1), thyroid (n = 1), Kaposi (n = 1) exposure; this is consistent with previous reports of high coincidences between melanoma and keratinocyte carcinoma (15). While previous studies have not investigated malignancy risk in individuals who develop frequent BCCs, one longitudinal study of 190,000 individuals in Denmark identified an increased risk of internal malignancy after the diagnosis of one or more BCC (16).…”
supporting
confidence: 89%
“…Other personal history of cancers included seminoma (n = 2), bladder (n = 1), thyroid (n = 1), Kaposi (n = 1) exposure; this is consistent with previous reports of high coincidences between melanoma and keratinocyte carcinoma (15). While previous studies have not investigated malignancy risk in individuals who develop frequent BCCs, one longitudinal study of 190,000 individuals in Denmark identified an increased risk of internal malignancy after the diagnosis of one or more BCC (16).…”
supporting
confidence: 89%
“…We previously reported an increased risk for cancer associated with history of KC, including melanoma in men and breast cancer, lung cancer, and melanoma in women. 7 In addition, Wu et al recently reported that a personal history of KC was associated with increased risk for melanoma (hazard ratio [HR], 2.22; 95% confidence interval [CI], 1.73-2.85), 8 which is consistent with previous reports from registry-based, case-control, and prospective cohort studies. [9][10][11][12] Although the association of a personal history of KC with melanoma risk has been consistently reported, its association with melanoma mortality remains undetermined.…”
supporting
confidence: 82%
“…For two of these cohorts, information on phenotype was not collected at baseline but rather in later surveys (Cho et al, 2005a;Freedman et al, 2003). None of the prospective studies examined skin phototype (burning/tanning) in relation to melanoma risk, only two studies recruited both women and men (Freedman et al, 2003;Wu et al, 2017), and none considered both in situ and invasive melanoma. Only two studies have presented estimates of effect separately for melanoma of different body sites (Cho et al, 2005a;Nielsen et al, 2012), and one of these was a cohort of women only (Nielsen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%